Does the Russian Industry Need Skilled Labour? Evidence from Recent History - ГимпельсонВладимир Ефимович (Journal of Economic Sociology, 2010)
The article is devoted to the problem of demand for skilled labour in Russian industrial production. Author demonstrates that in 2000–2009 the aggregate supply of labour of workers with diverse vocational education signiﬁ cantly increased while the aggregate demand for these categories of workers signiﬁ cantly decreased. At the same time industrial enterprises started complaining about a scarcity of skilled labour. And these complaints were getting more pronounced over time. These complaints were reﬂ ected in a variety of research micro-data sets as well. They began to affect governmental social and educational policy.However, how can we explain the increasing gap between macro- and micro-data? Using large-scale surveys of industrial enterprises conducted in 2003, 2005 and 2009, the author demonstrates that scarcity of the skilled labour is largely imaginary. It is explained by a number of institutional subversions in the Russian economy which stimulate employee turnover, undermine motivation toward vocational training, allow inefﬁ cient enterprises to be aﬂ oat and support highly differentiated salary levels among homogenous companies